Price Policy and Taxation as Effective Strategies for Tobacco Control - Richard Felsinger; Ernest Groman (Frontiers Media S.A., 2022)
ObjectiveOnly 13% of the world's population are living in countries imposing appropriate tobacco tax-rates. This study aims to promote the implementation of price policy measures as a striking tobacco control strategy in Austria and to encourage other countries to further increase their taxes to WHO best-practice levels.MethodThis study used the yearly economic data from Austria from 1997 to 2015. Applying a model for regression analysis, the price elasticity of total tobacco consumption was estimated.ResultsBetween 1997 and 2015 the price elasticity of demand for tobacco products (including cigarettes, cigars, and other tobaccos) was −0.661, however, the result is statistically insignificant. When excluding 2 anomalous years and removing a variable of the regression model the elasticity was −0.691 and statistically significant, indicating that a 1% increase in tobacco prices will result in a 0.691% decrease of tobacco consumption.ConclusionThe responsiveness of Austrian smokers to price changes has increased during the last decades. Because other activities showed no significance in the analysis, this study should encourage countries world-wide to use price policy and taxation more intensively in order to reduce smoking rates effectively.